Giant oral lipoma: a rare case report involving the masseter muscle - Macedo, Priscila Faquini; Medeiros, Yuri de Lima; Oliveira, Dandara; Santos, Lívia Marques; Marlière, Daniel Amaral Alves (Journal of Oral Diagnosis, 2024)
Lipoma is a benign neoplasm that primarily affects middle-aged individuals and is rare in the maxillomandibular region. Most lipomas are between 2 and 15 mm in diameter. Although rare, they can reach large dimensions and cause aesthetic and functional problems such as dysphonia, dysphagia, and facial asymmetry. We report a case of an extensive lipoma invading the masseter muscle region with a 2-year history in a 36-year-old man who underwent surgery under general anesthesia. A well-circumscribed neoplasm composed of mature adipocytes with a thin fibrous capsule was seen on histopathology analysis. The 6-month follow-up showed good healing without recurrence.